2020
DOI: 10.12998/wjcc.v8.i17.3786
|View full text |Cite
|
Sign up to set email alerts
|

Awareness and attitude of fecal microbiota transplantation through transendoscopic enteral tubing among inflammatory bowel disease patients

Abstract: BACKGROUND Transendoscopic enteral tubing (TET) has been used in China as a novel delivery route for fecal microbiota transplantation (FMT) into the whole colon with a high degree of patient satisfaction among adults. AIM To explore the recognition and attitudes of FMT through TET in patients with inflammatory bowel disease (IBD). METHODS An anonymous questionnaire, evaluating their awareness and attitudes toward FMT and TET was distributed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 31 publications
1
8
1
Order By: Relevance
“…Our study showed that IBD patients were interested in FMT but low awareness and acceptance, which is consistent with the results of domestic and international studies [22][23][24].The most preferred route for patients to receive FMT treatment in this study was oral fecal capsules (50.97%), which may be related to convenience and good tolerability [25]. However, anesthesia colonoscopy was preferred by 77% of UC patients in Kahn 's study [26] and 49.7% of CD patients in Zeitz's study [27].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our study showed that IBD patients were interested in FMT but low awareness and acceptance, which is consistent with the results of domestic and international studies [22][23][24].The most preferred route for patients to receive FMT treatment in this study was oral fecal capsules (50.97%), which may be related to convenience and good tolerability [25]. However, anesthesia colonoscopy was preferred by 77% of UC patients in Kahn 's study [26] and 49.7% of CD patients in Zeitz's study [27].…”
Section: Discussionsupporting
confidence: 91%
“…Drug infusion is facilitated by colonoscopy while minimizing psychological discomfort, but bowel preparation can be found unbearable by some patients [28]. The Transendoscopic enteral tubing(TET) route has also been proposed as a solution to the limitations of repeated FMT in a short period of time, avoiding intestinal injury and bleeding caused by repeated insertion of enema tubes or colonoscopy [23,29]. Nevertheless, only 5.81% of patients in our study chose the TET, due to the low awareness of TET in patients with IBD .…”
Section: Discussionmentioning
confidence: 99%
“…With regard to the lower gastrointestinal route of FMT administration, the latest progress is colonic TET, which is a safe, convenient, and reliable procedure for FMT that results in a high degree of patient satisfaction [ 22 , 23 ]. The experience of FMT through TET of patients with IBD leads them to maintain a positive attitude towards FMT [ 24 ]. Therefore, FMT delivery methods need to be rationally designed taking into account efficacy and recipient factors.…”
Section: Discussionmentioning
confidence: 99%
“…It was proven to be a safe and convenient procedure for multiple FMTs and colonic medication administration for patients aged over 7 years old [136] . According to a survey, patients who had undergone FMT by TET were more likely to recommend FMT than patients who had not [137] . Zhong et al [138] also reported that colonic TET was a safe and convenient delivery method in children aged 3–7 years.…”
Section: Methodology Of Fmtmentioning
confidence: 99%
“…[136] According to a survey, patients who had undergone FMT by TET were more likely to recommend FMT than patients who had not. [137] Zhong et al [138] also reported that colonic TET was a safe and convenient delivery method in children aged 3-7 years.…”
Section: Routes Of Deliveringmentioning
confidence: 99%